The Influence of Financial Statement variables on the Stock Price of Pharmaceuticals Sub Sector Companies - Sudirman,; Kamaruddin,; Salleh, Maisyarah Stapah @; Padli, Jaharudin (The journal of contemporary issues in business and government, 2021)
This study aims to examine the effect of Price Earnings Ratio (PER), Earnings Per Share (EPS), Price to Book Value (PBV), and Return on Equity (ROE) on Company Stock Prices in the Jakarta Islamic Index group on the Indonesia Stock Exchange. In this study panel data was conducted on secondary data obtained from the financial statements of the Pharmaceutical Sub-Sector companies, which amounted to 11 issuers in the 2015-2020 period. The analytical tool used is multiple regression analysis. In this study it was found that Price Earnings Ratio and Return on Equity, and Earnings Per Share simultaneously affected stock prices in Pharmaceutical Sub-Sector companies on the Indonesia Stock Exchange (IDX). Meanwhile, partially Price Earnings Ratio has no effect on the stock prices of Basic Industry sector companies on the Indonesia Stock Exchange (IDX). Next, the current ratio and debt to asset ratio affect the company's stock price in the Basic Industry sector on the Indonesia Stock Exchange (IDX).